ANALISIS DAYA SAING DAN KEBIJAKAN BEA KELUAR PADA KOMODITAS KAKAO (Theobroma cacao) INDONESIA - Ramadhani, Rifqi Aulia; Rifin, Amzul; Novianti, Tanti (Analisis Kebijakan Pertanian, 2024)
The export duty policy implemented in 2010 caused Indonesian cocoa bean exports to experience a decline in both quantity and value, while expoprt of cocoa bean derivative products (butter, powder, and paste) increased in term of quantity and value. However, imports of Indonesian cocoa beans were on the rise. This research aims to analyze the export duty policy for Indonesian cocoa beans based on the competitiveness of cocoa beans and their derivative products in the international market. Data were analyzed using the Porter’s Diamond Model method with Indonesian cocoa commodity stakeholders as respondents. The research results indicate that the analysis conducted using the Porter’s Diamond Model method reveals that the most important factors in enhancing the competitiveness of cocoa beans and their derivative products are demand factors, company strategy, structure and competition, and opportunity factors. Managerial implications that can be carried out by the cocoa industry and the government to improve the quality of cocoa beans and the competitiveness of processed cocoa bean products are related to the role of educational and training institutions in developing a skilled workforce, the utilization of processing technology to manage cocoa and enhance the competitiveness of Indonesian cocoa, government policies aimed at increasing national cocoa production, and export duty policies that require balance by improving the quality and maintenance of the upstream cocoa industry.